Pengembangan Media Video Storyline untuk Pembelajaran Sejarah Siswa Kelas X MIPA I di SMAN 3 Kerinci - Padlan Dwi Cahyo; Hera Hastuti (Jurusan Sejarah FIS UNP, 2020)
This study aims to improve the quality of learning of students and provide alternative uses of media in the form of understanding and benefits in using video media in the form of storyline which is motivated by the lack of media use in history learning, especially video media. This type of research is 4-D by using 3 stages from 4 stages of the development model, namely defining, designing, and developing. The design in making this video storyline media using the movavi video editor application and combining it with other applications. The subjects of this study consisted of 2 lecturers namely material experts and media experts, 2 history subjects, and 17 students of Class X MIPA I at SMAN 3 Kerinci. The object of this research is video storyline media. This research data is in the form of primary data that is data obtained from the questionnaire validity and practicality. The data analysis technique of this study was to use qualitative analysis in a descriptive form. This research produces an effective video storyline media used as a medium in learning history and can improve students' understanding in the history learning process based on data analysis obtained from the results of the validity and practicality test.